Penerapan Kearifan Lokal Samosir dalam Mengeksplorasi Bentuk-Bentuk Geometri - Mailani, Elvi; Saragih, Doni Irawan; Lubis, Fadila Putri; Siregar, Nurhasanah Br; Sihombing, Sartika Putri Ruth Angel; Simanjuntak, Sela (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to investigate how the Batak people in Samosir use their local knowledge to understand geometric shapes. The literature review research method, which is a data collection strategy focused on the evaluation of relevant and current scientific literature related to the research problem, is used in this publication. The data sources in the study came from Google Scholar, Scopus, and SINTA. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the data analysis show that the way local knowledge is applied to the study of geometric forms shows how Batak culture has used geometric principles in religious ceremonies as well as art and construction. In addition to having a practical and aesthetic purpose, these geometric shapes have a deep philosophical feel that enhances the cultural identity and bond of the community with nature and its ancestors. Through the local wisdom of the Batak people in Samosir, geometric ideas have been successfully identified and applied to various parts of their lives, including traditional house buildings, traditional artifacts, and ulos weaving crafts. Overall, this study shows how the concept of geometry is used organically by Batak local wisdom, which is essential for preserving community peace, fostering cultural identity, and fostering spiritual ties with nature and ancestors.